INFLUENCE OF CALCIUM HYDROXIDE CONCENTRATION ON THE SYNTHESIS NANOSIZED PRECIPITATED CALCIUM CARBONATE - Nooririnah, Omar; muhamad azwar, azhari; Umar , Al-amani; Yusliza, Yusuf; Mohd faiz , wahid (2014)
The precipitated of calcium carbonate has attracted much attention because of its numerous applications in various areas of plastics, textiles, rubbers, adhesives, paints and waste water treatment. Nanosized of precipitated calcium carbonate, (PCC) will enhance the properties and give better performance. Its high purity and close controlled particle size and shape are making it the white filler of choice. Nanosized precipitated calcium carbonate particles were prepared using spraying method. The particles were prepared using three (3) different concentrations of Calcium Hydroxide, Ca(OH)2, three (3) CO2 flow rate and three (3) different calcinations temperatures. The three (3) concentration of Calcium Hydroxide that been used are 25g / 200ml, 25g / 400ml and 25g / 800ml and each of these initial solution sprayed at three (3) different CO2 flow rate, 5l / per-minute, 7l / per-minute and 10l / per-minute. Calcium Carbonate, CaCO3 powders were then calcined at three (3) different temperature, 1100°C, 1200°C and 1300°C. Images from FESEM showed morphology of the particles changed to spindle-like or prismatic when the ionic strength of the Calcium Hydroxide, Ca(OH)2 was increased.